Verbal expression of pain A simple on leukemia’s patients in Lattakia - Sakor, Sam; Houseen, Fras (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
It is a necessary objective to control the pain and the overall evaluation of cancer patient. Therefore; this research aimed to identify the verbal expressions of pain of Leukemia patients through words and descriptions they use to describe their perceived pain. the research aimed too to compare the sensor and emotional expressions of their pain according to time of their diagnosis. The descriptive approach was adopted, and the Saint-Antoine questionnaire (QDSA) was used to measure sensory and emotional verbal expressions of pain. (42) Leukemia patients were tested in the cancer department in Tishreen Hospital in Latakia governorate, including (20) males and (22) females with diagnostic aged between (40 and 65). the results showed that there is difference between patients according to the time of diagnosis in number, deepness and intensity in choosed words for those patients that are in their early diagnosis stage.